Indigenous knowledge on medicinal plants used by the people of Kristi Village, Pokhara, Nepal - Upadhaya, Harilal (Himalayan Biodiversity, 2018)
The medicinal knowledge of plants is very common among the tribal people but much of the information is not yet documented. The purpose of the present study was to document information on medicinal plants used by the people of Kristi village, Pokhara, Nepal. A total of 42 medicinal plant species belonging to 39 genera and 29 families were documented each with local name, uses and mode of administration. The study indicated that the indigenous people widely accepted the traditional knowledge on the utilization of medicinally important plants.